Development of The Tanjung Pandan Old Town Area as a Heritage and Gastronomy Tourist Attraction - Pratiwi, Yunisti; Wahyuni, Eka Indah (JELAJAH: Journal of Tourism and Hospitality, 2024)
The purpose of study This is for know history and philosophy and tradition Culture Good in the form of reserve culture and food traditional, as well For know How strategy development so that become Power pull Heritage and Gastronomy Tourism in Tanjung Pandan City. The type of research used is qualitative. Research results This will describe history and the philosophy and development strategies implemented with hope existence effort This Can make become Tourist Attraction​ especially heritage and gastronomy which are interesting and in demand by tourists.